WEBSITE SISTEM INFORMASI PEMETAAN CAGAR BUDAYA KOTA SERANG, PROVINSI BANTEN - Sari Lalita; Ery Dewayani; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Serang city is one of the many cities that are in the region of Indonesia with a variety of attractions, some of which can be regarded as a cultural heritage. But until now, the cultural heritage of Serang City is still not so well known by the wider community. Therefore, required a media that is able to introduce the cultural heritage of Serang City to be better known through the making of the website.A “Serang City Cultural Heritage Mapping Information System Website, Banten Province